1987
DOI: 10.1128/iai.55.5.1144-1150.1987
|View full text |Cite
|
Sign up to set email alerts
|

Comparative virulence of intra- and interstrain lipopolysaccharide variants of Coxiella burnetii in the guinea pig model

Abstract: We compared the relative infectivity and virulence of lipopolysaccharide (LPS) variants of the Nine Mile strain of Coxiella burnetii with those of the Priscilla strain, a representative of endocarditis-type strains. In agreement with results of previous studies, Nine Mile phase I (9mi/I) organisms were highly infectious, eliciting seroconversion and fever with inocula containing as few as four organisms. Viable 9mi/I was recovered from the spleens of infected animals 30 days postinfection. Nine Mile phase II (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(125 citation statements)
references
References 32 publications
6
112
0
6
Order By: Relevance
“…All C. burnetii isolates are not the same (Moos & Hackstadt, 1987;Kazar et al, 1993) so we decided to test 3/3 10 À6 3/3 10 À7 3/3 2/3 10 À8 1/3 0/3 10 À9 1/3 0/3 10 À10 0/3 0/3 10 À11 0/3 10 À12 0/3 DD 50 1.5 9 10 8 1.5 9 10 7 DD 50 , qPCR detection dose 50.…”
Section: Discussionmentioning
confidence: 99%
“…All C. burnetii isolates are not the same (Moos & Hackstadt, 1987;Kazar et al, 1993) so we decided to test 3/3 10 À6 3/3 10 À7 3/3 2/3 10 À8 1/3 0/3 10 À9 1/3 0/3 10 À10 0/3 0/3 10 À11 0/3 10 À12 0/3 DD 50 1.5 9 10 8 1.5 9 10 7 DD 50 , qPCR detection dose 50.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of biological differences of the phase variants has been studied in various ways, but a clear difference of the virulence in vivo was only found for pyrogenicity in guinea pigs 8 and may result from LPS O-side-chain differences. In this study, we showed difference of phase I and II C. burnetii virulence in pathology for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…This is required to favour the autophagymediated homotypic fusion between CCVs. Although not a Cvp, Cig57 interacts with the clathrin adaptor FCHO2 at clathrin-coated pits and reroutes clathrin-mediated membrane traffic to the CCV (NMII) of the Nine Mile Phase I strain (NMI), presenting a single deletion of 21 genes involved in lipopolysaccharide biosynthesis and displaying loss-of-virulence phenotype in animal models (Moos and Hackstadt, 1987;Hoover et al, 2002). Thus, NMII was allowed for manipulation in biosafety level-2 (BSL-2) environments ( Figure 2D), as opposed to other C. burnetii strains that require manipulation in…”
Section: The Long and Winding Road (To Genetic Manipulation)mentioning
confidence: 99%